Does using PAs in the closed treatment of pediatric forearm fractures increase malunion risk?. Issue 12 (December 2017) - Garrison, Stephanie; Eismann, Emily A.; Cornwall, Roger
ABSTRACT: Purpose: This study assessed whether using physician assistants (PAs) for fracture follow-up during nonoperative management of pediatric forearm fractures was associated with an increased risk of malunion. Methods: The study was a retrospective review of charts of 141 children under age 18 years who were treated nonoperatively in the division of orthopedics over 12 months for forearm fractures. The effect of type and number of follow-up providers on risk of malunion was determined and controlled for fracture type, location, and initial angulation. Logistic regression, Fisher exact test, and Cochran-Armitage trend test were used to analyze the data, with P < .05 indicating statistical significance. Results: Using strict criteria, malunion was identified in 42 (30%) of 141 patients. Follow-up provided by even up to four PAs did not increase malunion risk. Transfer of care between two attending physicians increased malunion risk, independent of fracture characteristics. Conclusion: The involvement of even multiple PAs during follow-up management of nonoperatively treated pediatric forearm fractures is not associated with an increase in the risk of malunion. These findings are consistent with previous published works that highlighted the safe and valuable role PAs can play in the management of common fractures.